2007
DOI: 10.1152/ajprenal.00201.2006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting albumin glycation attenuates dysregulation of VEGFR-1 and collagen IV subchain production and the development of renal insufficiency

Abstract: CW. Inhibiting albumin glycation attenuates dysregulation of VEGFR-1 and collagen IV subchain production and the development of renal insufficiency. Am J Physiol Renal Physiol 292: F789 -F795, 2007. First published October 3, 2006; doi:10.1152/ajprenal.00201.2006.-Glomerular cells in culture respond to albumin containing Amadori glucose adducts (the principal serum glycated protein), with activation of protein kinase C-␤1, increased expression of transforming growth factor (TGF)-␤1, the TGF-␤ type II signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 37 publications
5
25
1
Order By: Relevance
“…Urine albumin values were lower at study end compared to baseline in all of the microalbuminuric patients receiving GLY-230, whether or not they were being treated with an ACE inhibitor or AR blocker. This encouraging finding replicates results in experimental animals [26,27] and, in the prompt response to a 2-week course of study drug, resembles the precedent established for reduction of albuminuria with relatively short-term therapeutic intervention reported with the renin inhibitor aliskiren [30]. In that study of 15 patients with type 2 diabetes, aliskiren reduced the urine albumin/creatinine ratio after 2–4 days of treatment [30]; patients were given furosemide, but previous medications were discontinued before enrollment, whereas in the present study patients being treated with an ACE inhibitor or ARB continued to receive these agents.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Urine albumin values were lower at study end compared to baseline in all of the microalbuminuric patients receiving GLY-230, whether or not they were being treated with an ACE inhibitor or AR blocker. This encouraging finding replicates results in experimental animals [26,27] and, in the prompt response to a 2-week course of study drug, resembles the precedent established for reduction of albuminuria with relatively short-term therapeutic intervention reported with the renin inhibitor aliskiren [30]. In that study of 15 patients with type 2 diabetes, aliskiren reduced the urine albumin/creatinine ratio after 2–4 days of treatment [30]; patients were given furosemide, but previous medications were discontinued before enrollment, whereas in the present study patients being treated with an ACE inhibitor or ARB continued to receive these agents.…”
Section: Discussionsupporting
confidence: 90%
“…Coupled with the finding that glycated albumin decreases nephrin production [20] and that GLY-230 restores glomerular nephrin in genetically diabetic mice [26,27], it is reasonable to postulate that the lessening of albuminuria accompanying reduction in glycated albumin reflects improved podocyte health/nephrin production, although renal biopsy, which is obviously far beyond the scope of the present study, would be required for confirmation.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Very recent studies suggested that VEGF secreted from podocytes might act as an autocrine factor on both itself and endothelial cells [13]. The upregulation of VEGF expression was detected in various human and experimental renal diseases [14, 15], and the blockage targeted to VEGF signaling could reduce proteinuria in several models of diabetic nephropathy [16, 17]. These results implied that VEGF played important deleterious roles in the occurrence and development of proteinuria.…”
Section: Introductionmentioning
confidence: 99%